Two new species of tortricid moths (Lepidoptera: Olethreutinae: Olethreutini) injurious to Picea crassifolia in China - Niu, Zehua; Li, Yange; Song, Xueling; Ma, Yanfang; Yu, Haili (Zootaxa, 2024)
Two new species of the genus Pseudohermenias, P. absimilis sp. nov. and P. linxica sp. nov., are described from China. They feed on Picea crassifolia in the northwestern regions of the country. Photographs of the adult specimens and their genitalia are provided. Keys to the species of the genus based on the male and the female genitalia are presented.